2002
DOI: 10.1179/016164102101199783
|View full text |Cite
|
Sign up to set email alerts
|

Nonenzymatic derived lipid peroxide, 8-iso-PGF, participates in the pathogenesis of delayed cerebral vasospasm in a canine SAH model

Abstract: We studied whether 8-iso-PGF2alpha, nonenzymatic arachidonyl peroxide, participated in the pathogenesis of delayed vasospasm using a canine subarachnoid hemorrhage (SAH) model. Fourteen adult mongrel dogs were divided into two groups, two-hemorrhage SAH group (n = 8) and control group (n = 6). The contents of 8-iso-PGF2alpha in CSF, the basilar artery segment, and subarachnoid clot were measured by enzyme immunoassay kit. The CSF 8-iso-PGF2alpha content on Day 7 in the SAH group was 67.9+/-29.9 pg ml(-1) (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 18 publications
3
17
0
Order By: Relevance
“…It is likely that the release of vasoconstrictor mediators by clotting blood plays a major role in triggering the fall in CBF after SAH. This conclusion is further supported by previous findings that the levels of endothelin (46), thromboxane (36), ATP (31), isoprostanes (44), glutamate (4), PAF (18), and 5-HT (6,43) in CSF all increase after SAH. In addition, this view is consistent with the evidence that cerebral vasospasm after SAH is attenuated by inhibitors of endothelin synthesis or receptors (10, 12), 5-HT receptor antagonists (6), and inhibitors of downstream second messengers of cerebral vasoconstriction, including Ras, Rho, MAPK, and PKC (25,26,33,52).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…It is likely that the release of vasoconstrictor mediators by clotting blood plays a major role in triggering the fall in CBF after SAH. This conclusion is further supported by previous findings that the levels of endothelin (46), thromboxane (36), ATP (31), isoprostanes (44), glutamate (4), PAF (18), and 5-HT (6,43) in CSF all increase after SAH. In addition, this view is consistent with the evidence that cerebral vasospasm after SAH is attenuated by inhibitors of endothelin synthesis or receptors (10, 12), 5-HT receptor antagonists (6), and inhibitors of downstream second messengers of cerebral vasoconstriction, including Ras, Rho, MAPK, and PKC (25,26,33,52).…”
Section: Discussionsupporting
confidence: 87%
“…Superoxide radicals at low concentration have been reported to constrict vessels in several vascular beds in part by decreasing the levels of nitric oxide (NO) (13,42), and there is a recent report that supports a similar mechanism in cerebral arteries (55). Free radicals also increase the production of lipid peroxides and isoprostanes (20,44) that are potent constrictors of cerebral arteries (19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We previously showed that 8-ISO level, which is a sensitive indicator of tissue lipid peroxidation (LPO) concentration (Wood et al, 2003), increased in lungs, in agreement with other data (Razavi et al, 2005). In the present study, the increase in tissue 8-ISO levels after carrageenan injection correlates with other experimental studies (Basu et al, 2001;Chung et al, 2011;Sakamoto et al, 2002). Agonist administration decreased 8-ISO levels in paw tissue, prompting us to think that stimulation of 5-HT 7 receptors protected paw tissue by reducing oxidative stress.…”
Section: Discussionsupporting
confidence: 91%
“…Like the contamination of the kidney with Mb, the CSF is contaminated with Hb. With a reduced antioxidant capacity, oxidative damage occurs that may lead to the formation of IsoPs in the CSF (235). Also, like that of rhabdomyolysis, we have shown by HPLC that the respiratory hemoprotein in the CSF is modified such that a percentage of the protein is in the heme-to-protein cross-linked form, demonstrating that Hb undergoes redox cycling in the CSF (Fig.…”
Section: Reedermentioning
confidence: 93%